Decolonizing global health: a scoping review - Deena Mehjabeen; Kyle Patel; Rahul M. Jindal (BMC Health Services Research)
Abstract We summarize research on decolonizing global health and highlight existing gaps, including the lack of a formal definition and clear aims for the movement. We examine the decolonization of global health curricula and authorship in indexed journals, aiming to build a shared understanding among global health scholars. The review included studies from all global regions to ensure comprehensive geographical representation. Of the 155 identified records, most were published from 2021 onward and predominantly originated from the Global North. Studies focusing solely on racism were excluded. Additionally, non-English publications and studies prior to 2019 were excluded, which may have limited insights from other perspectives, such as those available in Spanish from Latin America. The included studies centered on topics such as curricula, the COVID-19 pandemic, and equity in authorship for Global South scholars. However, despite these discussions, voices from the Global South remain underrepresented in indexed journals, and there is limited focus on actionable strategies for shifting power dynamics to foster true decolonization in global health governance and funding. To address these issues, we recommend mentorship programs targeted at academics from the Global South, focusing on research capacity-building, grant writing, and leadership development. We call for broader structural reforms, including equitable funding allocation, the decolonization of research agendas, and the dismantling of hierarchical systems that privilege voices from the Global North over the Global South. The creation of collaborative networks focused on decolonization is critical in demonstrating a commitment to dismantling oppressive systems and fostering equity. While some progress has been made, further research is needed to explore how funding, knowledge systems and publishing can be more equitably distributed, supporting a truly decolonized global health agenda that advances social justice and health equity.